Chronotherapy in head and neck cancer: A systematic review and meta‐analysis - Mohammad Abusamak (10712848) (2024)
Optimizing the timing of radiotherapy and chemotherapy tailored to the body's biological clock (i.e., chronotherapy) might improve treatment efficacy and reduce side effects. This systematic review evaluated the effect of chrono‐radiotherapy and chrono‐chemotherapy on treatment efficacy, toxicity and adverse events in head and neck cancer (HNC) patients from prospective and retrospective studies published between the date of database inception until March 2024. The primary outcome measures for chrono‐radiotherapy were treatment efficacy and incidence of grade ≥3 oral mucositis, and the main outcome measures for chrono‐chemotherapy were objective response rate (ORR) and overall toxicity and adverse events. Of 7349 records identified, 22 studies with 3366 patients were included (chrono‐radiotherapy = 9 and chrono‐chemotherapy = 13). HNC patients who underwent chrono‐radiotherapy had 31% less risk of developing severe oral mucositis (grade ≥3) compared to evening radiotherapy (risk ratio: 0.69, 95% CI: 0.53–0.90, p < 0.05). Further, HNC patients who underwent chrono‐chemotherapy using platinum‐based and antimetabolite agents had 73% less risk of lower ORR compared to nontime‐stipulated chemotherapy (risk ratio: 0.27, 95% CI: 0.09–0.84, p < 0.05). In addition, HNC patients who underwent chrono‐chemotherapy had 41% less risk of lower overall toxicity and adverse events in comparison to nontime‐stipulated chemotherapy (risk ratio: 0.59, 95% CI: 0.47–0.72, p < 0.05). In conclusion, chrono‐chemotherapy studies showed evidence of improved treatment efficacy, while in chrono‐radiotherapy it was maintained. Chrono‐radiotherapy and chrono‐chemotherapy studies provide evidence of reduced toxicity and adverse events. However, optimized circadian‐based multicentric clinical studies are needed to support chrono‐radiotherapy and chrono‐chemotherapy in managing HNC. Other Information Published in: International Journal of Cancer License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/ijc.35234